Degrowth, modernity, and the open society - Sebastian Strunz; Bartosz Bartkowski (Helmholtz-Zentrum für Umweltforschung (UFZ), 2017)
Critiques of modernity often align with critiques of the existing institutions of lib-eral democracy. We argue that the degrowth movement can learn from the experience of past critiques of modernity by avoiding their major mistake - that is, (inadvertently) conflating a critique of modernity with a rejection of liberal democratic institutions. Hence, we suggest to frame degrowth as the promotion of new vocabularies within a deliberative account of democ-racy. Specifically, we proceed in three steps: first, we briefly review some essential critiques of modernity and their stance towards liberal democracy. Second, we illustrate how some of the argumentative patterns within the degrowth literature may inadvertently endanger core values of the open society. Third, we introduce our perspective on a liberal degrowth that aims to fulfil the "unfinished project of modernity".
Keywords: 330